2017
DOI: 10.1002/anie.201612290
|View full text |Cite
|
Sign up to set email alerts
|

A General and Highly Selective Cobalt‐Catalyzed Hydrogenation of N‐Heteroarenes under Mild Reaction Conditions

Abstract: Herein, a general and efficient method for the homogeneous cobalt-catalyzed hydrogenation of N-heterocycles, under mild reaction conditions, is reported. Key to success is the use of the tetradentate ligand tris(2-(diphenylphosphino)phenyl)phosphine). This non-noble metal catalyst system allows the selective hydrogenation of heteroarenes in the presence of a broad range of other sensitive reducible groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 91 publications
(50 reference statements)
0
71
0
Order By: Relevance
“…In addition, the common metal-based Lewis acids failed in promoting this reaction (entries 5-7). The unique catalytic activity of B(C 6 F 5 ) 3 may be attributed to its ability to form af rustrated Lewis pair with acarboxyl group to activate the hydrosilane, [11c] which derives from both the Lewis acid center, that is, electrophilic borane, and large steric hindrance of B(C 6 F 5 ) 3 .S ubsequently, varioush ydrosilanes were investigated for the reductive alkylation of 1a with formic acid (entries 4a nd [8][9][10][11][12]. PMHS (polymethylhydrosiloxane), Ph 3 SiH, and PhSiH 3 were found to be inactive (entries8-10).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition, the common metal-based Lewis acids failed in promoting this reaction (entries 5-7). The unique catalytic activity of B(C 6 F 5 ) 3 may be attributed to its ability to form af rustrated Lewis pair with acarboxyl group to activate the hydrosilane, [11c] which derives from both the Lewis acid center, that is, electrophilic borane, and large steric hindrance of B(C 6 F 5 ) 3 .S ubsequently, varioush ydrosilanes were investigated for the reductive alkylation of 1a with formic acid (entries 4a nd [8][9][10][11][12]. PMHS (polymethylhydrosiloxane), Ph 3 SiH, and PhSiH 3 were found to be inactive (entries8-10).…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, we speculated that carboxylic acid could also act as alkylating agent to run reductive C−C bond couplings. To the best of our knowledge, direct synthesis of BIM from indole with carboxylic acid has not been explored and only a related example for the cobalt‐catalyzed alkylation of indole with carboxylic acid was described in which BIM was only identified as a byproduct (yield <5 %) . Notably, as a typical carboxylic acid, formic acid can be prepared from CO 2 through catalytic hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another promising strategy for the development of a more sustainable chemistry and particularly catalysis, representing as well an economic advantage, is the replacement of noble metal catalyst by non‐noble metal catalytic systems (Figure ) . Although there is still a long way to go in order to achieve such objective, some studies have reported the use of transition metal nanoparticles as hydrogenation catalysts with encouraging performance . For instance, Abe and coworkers have explore the replacement of Pt‐based catalysts by a supported Cu−Ni nanomaterial with potential applicability for gas phase reactions ,…”
Section: Catalysismentioning
confidence: 99%
“…Hence, many bioactive compounds based on this scaffold are used as drugs and agrochemicals, and some efforts have been devoted to their synthesis . In particular, tetrahydrobenzoquinolines have been synthesized by cycloaromatization, ring expansion, hydrogenation, and more recently by Au(I)‐catalysed formal [4+2] cycloaddition . In continuation of our studies on the chemistry and synthetic applications of lactam‐derived enol phosphates and triflates, we recently reported that N ‐protected‐2‐alkynyl tetrahydropyridines are versatile substrates for gold‐catalysed transformations.…”
Section: Introductionmentioning
confidence: 99%